2015
DOI: 10.1111/srt.12271
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, ultrasound, and videodermatoscopy monitoring of psoriatic patients following biological treatment

Abstract: VD and US may be useful to monitor psoriasis treatment. Further investigations are warranted to assess if the persistence of an altered vascular pattern despite clinical and US normalization, as observed in 22% of patients, may influence disease progression and/or correlate with rate and severity degree of relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 27 publications
2
36
1
1
Order By: Relevance
“…5). 14,23,24 Similar vasculature was observed in dermoscopy of psoriatic lesions located on glans penis. In 6 patients with psoriatic balanitis, Lacarrubba et al 17 reported homogenous, bushy vessels.…”
Section: Dermoscopy Of Psoriatic Lesions Of the Skinsupporting
confidence: 54%
See 3 more Smart Citations
“…5). 14,23,24 Similar vasculature was observed in dermoscopy of psoriatic lesions located on glans penis. In 6 patients with psoriatic balanitis, Lacarrubba et al 17 reported homogenous, bushy vessels.…”
Section: Dermoscopy Of Psoriatic Lesions Of the Skinsupporting
confidence: 54%
“…Also, the efficacy of therapy with biologics, with a good prognostic factor of purpuric dots, cyclosporine and long-term therapy with potent steroids, with patterns that indicate the overuse, was monitored by dermoscopy. 11,14,16,[19][20][21][22]56 While revising the literature, the authors noted the need of terminology unification which is subjective in terms, especially as regards studies concerning onychoscopic features of psoriasis. Further limitations of the present study were lack of histological confirmation of the disease in many cases and too small samples in some studies; moreover, the use of different dermoscopes may have influenced the results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vascular pattern evaluation by VD in psoriasis provides important information on the therapeutic response, showing normalization or persistence in clinically healed psoriatic plaques . Our results showed a higher mean capillary bush diameter in psoriatic plaques located on the lower legs, reflecting increased vascular flow.…”
supporting
confidence: 49%